(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the functional-semantic field and cognitive status of inchoativeness in Uzbek and English languages. It examines the theoretical foundations of inchoativeness, analyzing how this linguistic category is expressed in both languages and its functional and cognitive significance in speech. Differences and similarities between Uzbek and English are highlighted through linguistic examples, emphasizing the role of inchoativeness in structuring meaning and thought in communication. The study provides insights into the interaction of semantics and cognition, contributing to comparative linguistic studies.